Návrh marketingové strategie - Hlavica, Tomáš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2016)
V této diplomové práci je na základě teoretického rozboru provedena analýza vybrané firmy. Jedná se o střední firmu nabízející služby v oboru VZT, chlazení, klimatizací a systémů SHZ. Společnost doposud analýzy a strategické plánování neprováděla. Na základě analýzy firmy je pak v práci uvedena specifikace vizí a cílů společnosti, od nichž se odvíjí návrh marketingové strategie. Tato práce by tedy měla být podkladem právě pro zavedení strategického plánování společnosti.

The analysis of the selected company is accomplished based on theoretical analysis in this diploma thesis. It is a medium-sized company offering services in the field of HVAC, refrigeration, air conditioning systems and extinguishing systems. The company has not accomplished analyses and strategic planning so far. Visions and targets of the company is particularized based on analysis of company. Concept of marketing strategy come from these visions and targets. This thesis should be the fundament for implementation of this strategic planning.
Marketing Strategy Proposal
Keywords: Marketingová strategie; situační analýza společnosti; SWOT analýza společnosti; specifikace vizí firmy; specifikace cílů firmy; návrh marketingové strategie; kontrolní etapa.; Marketing strategy; situational analysis of the company; SWOT analysis of the company; specifications of vision of the company; specifications of targets of the company; concept of marketing strategy; supervisory period.